Acoustic Emission Characteristics and Initiation Mechanism of Instantaneous Rock Burst for Beishan Granite - Wang, Chaosheng; Wan, Hao; Ma, Jianjun; Chen, Xianglin (Shock and Vibration, 2024)
In this paper, the instantaneous rock burst test of Beishan granite is carried out by using a deep rock burst simulation test system and an acoustic emission monitoring system. The acoustic emission data were monitored in real time during the test. The variation of the number and energy of acoustic emission events was studied, and the distribution characteristics of rock burst debris were analyzed. Based on plate and shell mechanics, the failure process of surrounding rock is discussed from the perspective of structural stability. The results show that (1) when the vertical stress reaches 171.31 MPa, the specimen is destroyed and the number of acoustic emission events and cumulative absolute energy before the specimen is destroyed increase sharply. (2) The debris generated by rock burst is mainly composed of slab debris, flaky debris, and thin flaky debris, accounting for 93.53% of the total debris. (3) When the length or height of the rock slab is constant, the maximum tensile stress in the rock slab decreases nonlinearly with the increase of rock slab thickness. For the same size of the rock slab, the farther away from the roadway wall, the greater the maximum tensile stress in the rock slab. (4) When the thickness of the rock slab is constant, the maximum tensile stress in the rock slab increases nonlinearly with the increase of height to thickness ratio K. When the ratio of height to thickness K is constant, the maximum tensile stress in the rock slab increases with the increase of rock slab thickness h. (5) With the increase of covering depth, the critical failure thickness of the rock slab decreases nonlinearly and the surplus energy increases nonlinearly.